2018
DOI: 10.1111/padm.12407
|View full text |Cite|
|
Sign up to set email alerts
|

Formalization and consistency heighten organizational rule following: Experimental and survey evidence

Abstract: This study examines the attributes of organizational rules that influence rule following. Rule following fosters organizational effectiveness by aligning individual behaviours with organizational preference. While a range of theoretical explanations have been offered for rule following, the characteristics of rule design and implementation have received less empirical attention. Borrowing from the green tape theory of effective rules, this study examines the influence of two particular characteristics—rule for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 87 publications
(106 reference statements)
3
45
2
Order By: Relevance
“…Rapid and inconsistent changes have a negative impact on frontline workers’ perceptions of these policies and the government's legitimacy, and may even make them cynical or indifferent (Van Engen et al ). This conclusion aligns with previous studies that have shown that ‘what you see (in terms of formal policy) may not be what you get (in terms of policy‐as‐produced)’ (Brodkin , p. 943) and studies that have concluded that consistency heightens organizational rule‐following (Borry et al ).…”
Section: Discussionsupporting
confidence: 90%
“…Rapid and inconsistent changes have a negative impact on frontline workers’ perceptions of these policies and the government's legitimacy, and may even make them cynical or indifferent (Van Engen et al ). This conclusion aligns with previous studies that have shown that ‘what you see (in terms of formal policy) may not be what you get (in terms of policy‐as‐produced)’ (Brodkin , p. 943) and studies that have concluded that consistency heightens organizational rule‐following (Borry et al ).…”
Section: Discussionsupporting
confidence: 90%
“…Empirical research on rule bending and rule breaking indicates that a number of individual and organizational attributes may contribute to or spur these types of decisions in policy enactment. At the organizational level, both attributes of the agency and the organizational climate have been found to shape individual rule-bending tendencies (Borry, 2017; Borry et al, 2018; Brockmann, 2017; DeHart-Davis, 2007; Henderson, 2013a). DeHart-Davis (2007) found that aspects of organizational structure such as centralization and formalization, as well as perceptions of rules as onerous and unnecessary—as red tape—shape rule-bending behavior; centralization increases rule bending, whereas formalization reduces it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other words, quantitative judgments about organizational rules say little about the qualitative experience of them. In contrast, some recent studies have used an experimental approach to link specific administrative scenarios to relevant outcomes such as satisfaction (Kaufmann and Tummers, 2017;Tummers et al, 2016) and rule following (Borry et al, 2018). These studies do offer a few reasonable (though untested) conjectures about how specific rule qualities may lead to observed outcomes (for instance, rules that are written "focus attention and convey legitimacy" (Borry et al, 2018, p. 371)), however, they do not advance a fully articulated, generalized, and cognition-based account of the experience of organizational rules.…”
Section: Introductionmentioning
confidence: 99%